DIGITAL INTIMACY INTERFERENCE AMONG COUPLES IN RIVERS STATE, NIGERIA: IMPLICATIONS FOR MARITAL INTIMACY AND STABILITY - Eke, Chigozi; Ihejirika, Walter Chikwendu; Ochonogor, Christopher Ifeakachukwu (African Journal of Social and Behavioural Sciences, 2024)
The increasing prevalence of digital media usage and the influence of digital interactions on marital stability raise concerns about the potential interference in the intimacy of couples in Rivers State, Nigeria. Hence, this study examined the implications of digital intimacy interference for marital stability among couples in Rivers State. The theoretical framework of the study was drawn from the social penetration theory and social network interference theory. The research design adopted for this study was a descriptive survey design. The population for this study comprised married male and female residents of Rivers State from an age bracket of 18 and above. Therefore, the population for this study was 1,404,855. Krejcie and Morgan’s determinant table was used to obtain a sample of 384 respondents, and a multistage sampling method was used to obtain the respondents. The instruments used for data collection in this study were a set of questionnaires. The research questions were analysed, using descriptive statistical analysis. Data were analysed using percentages and weighted mean scores (WMSs). The Pearson product moment correlation coefficient (PPMC) was used to test the hypotheses. The findings revealed that the ways in which digital media interferes with intimacy in married couples were through distraction from quality conversations or bonding time in marriage, and through spending more time on digital devices than engaging in physical affection or intimate moments. The study therefore recommended that married couples should prioritize physical affect and set boundaries on digital device usage to foster a deeper connection within the marriage.